2013
DOI: 10.1159/000346694
|View full text |Cite
|
Sign up to set email alerts
|

Subacute Cutaneous Lupus Erythematosus Induced and Exacerbated by Proton Pump Inhibitors

Abstract: Background: Subacute cutaneous lupus erythematosus (SCLE) can be induced by numerous drugs. We report 3 cases of SCLE induced by proton pump inhibitors (PPIs). Objective: To highlight a rare cutaneous side effect induced by a frequently prescribed drug such as a PPI. Case Reports: Case 1 was a 30-year-old man who developed multiple annular plaques over the trunk and lower limbs 1 month after the initiation of pantoprazole. Antinuclear antibodies (ANA) were positive with anti-Ro/SSA and anti-La/SSB antibodies, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(8 citation statements)
references
References 13 publications
0
7
0
1
Order By: Relevance
“…A literature review of PPI-induced CLE using the PubMed online database identified 18 case reports of PPI-induced SCLE and one case of PPI-induced DLE. 5 , 12 , 15 23 However, the latter case did not fulfil the proposed definition of DILE, as the discoid lesions occurred after discontinuation of pantoprazole. In a Swedish case–control study of 234 patients with SCLE, 65 had received PPIs.…”
Section: Discussionmentioning
confidence: 94%
“…A literature review of PPI-induced CLE using the PubMed online database identified 18 case reports of PPI-induced SCLE and one case of PPI-induced DLE. 5 , 12 , 15 23 However, the latter case did not fulfil the proposed definition of DILE, as the discoid lesions occurred after discontinuation of pantoprazole. In a Swedish case–control study of 234 patients with SCLE, 65 had received PPIs.…”
Section: Discussionmentioning
confidence: 94%
“… 7 Jones et al (2015) [ 19 ] 73, F, African-American, USA Pantoprazole Forehead, neck, back, upper and lower extremities ANA+ (speckled), SSA+, SSB−, dsDNA−, histone− Amlodipine stopped (was provided with pantoprazole initially); amlodipine restarted after 1 month 1 month 8 Hung et al (2015) [ 20 ] 60, F, UK Omeprazole Trunk, thighs, back Previous history of SCLE, ANA+, SSA+ Prednisolone and mycophenolate mofetil 4 months 9 Almebayadh et al (2013) [ 21 ] 30, M (originally from island of Martinique) Pantoprazole 1 month Trunk, lower limbs ANA+ (speckled), SSA+, SSB+, histone− 8 weeks (relapsed when pantoprazole accidently re-challenged) 10 Almebayadh et al (2013) [ 21 ] 31, F (originally from Canada) Esomeprazole (20 mg/day) (no other treatment) 7 weeks Trunk, scalp, face Pregnant, ANA+ (speckled), SSA+, SSB−, histone− After discontinuing PPI, topical steroids and hydroxychloroquine 400 mg daily were started. After 2 weeks, oral steroid added (0.25 mg/kg/day) 4 weeks 11 Almebayadh et al (2013) [ 21 ] 57, F (originally from island of Martinique) Omeprazole Few weeks Trunk, upper and lower limbs ANA+, SSA+, anti-SM, anti-RNP antibodies Not mentioned 12 W...…”
Section: Resultsmentioning
confidence: 99%
“…[ 11 ] Since then, several case reports and case series of PPI-induced SCLE have appeared in literature. [ 7 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 ] PubMed search (limited to English literature) revealed 43 cases of PPI-induced SCLE, comprising 12 case reports of single patients and five reports of two or more patients. [ 7 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 ] A summary of these five case series compared to current series is tabulated in Table 3 .…”
Section: Discussionmentioning
confidence: 99%